D2 statistic technique used for analysis of genetic divergence among Gir crossbreds - Mote, Mahendra Gorakh; Narwade, Vishnu Eknath; Gaikwad, Ulhas Shivaji; Sakhare, Pramodkumar Shriram (Indian Journal of Dairy Science, 2020)
D2 analysis is used for selection of genetically divergent parents. The concept of D2 was originally developed by P. C. Mahalanobis in 1928. It is used to measure degree of diversification and determines relative portion of each component trait to total divergence. The study aimed to estimate the genetic divergence among FG (50% HF+50% Gir), IFG (FG Interse), FJG (50% HF+25% Jersey+25% Gir), IFJG (FJG Interse) and R (50% HF+12.50% Jersey+37.50% Gir) crosses of Gir on the basis of age at first calving, first calving interval, lactation milk yield, lactation length and lactation milk yield per day of calving interval using Mahalanobis D2 statistics. The genetic group differences were significant (P